Religion and identity politics Global trends and local realities - Matthews, Matthew; Tay, Melvin (Toh Tuck Link, Singapore World Scientific Publishing, 2021)
Discourse on fundamentalism has gained much attention in recent years, particularly in a post-9/11 context where extremist or terrorist threats are more prominent, perilous, and pervasive. This edited volume seeks to spotlight the perspectives of academics and practitioners vis-à-vis global trends in religious fundamentalism and right-wing extremism over the past decade. It presents a collection of works from notable academics and practitioners; including a selection of case studies from Asia to illustrate the contemporary interplay of religion, politics and identity; alongside broader global trends of religious fundamentalism.

The chapters that follow attempt to trace the sources and factors that led to the dramatic rise in these powerful forces of faith, which influence societies and politics around the world. Together, they present a carefully curated narrative of the interplay of religion and identity politics globally and across Asia. The prevailing differences in demographics, history and the extent of ethno-religious diversity across country contexts are perused across each chapter, and the ensuing circumstances deliberated upon.

As these circumstances change, the ways people interpret their identities, engage in politics, and navigate their religion will also evolve. How we manage the effects of religious fundamentalism must hence begin with an understanding of how religion, identity, and politics interact — and this is what the upcoming chapters seek to illustrate.
Acknowledgements
Preface
Introduction: Perusing the Contemporary Interplay of Religion and Politics (Mathew Mathews and Melvin Tay)
Part I Global Synopses:
Chapter 1 Fundamentalist Extremism and Politics (Jonathan Fox)
Chapter 2 The Global Rise of Religious Nationalism (Mark Juergensmeyer)
Part II Asian Case Studies:
Chapter 3 An Alternate State of Faith: The Rise of Militant Christians in the Philippines (Alex B. Brillantes, Jr., Maria Pilar Lorenzo and Alicia Wang Sin)
Chapter 4 Malaysia: Identity Politics, the Rise of Political Islam and Ketuanan Melayu Islam (James Chin)
Chapter 5 Who are Indonesia's Islamist Majoritarians and How Influential are They? (Daniel Peterson and Saskia Schäfer)
CHapter 6 Politically Motivated Religious Violence in Asia: Sri Lanka, A Case Study (Rohan Gunaratna)
Part III Practitioner Perspectives:
Chapter 7 Identity: Religion, Politics or Something Else? (Bilahari Kausikan)
Chapter 8 The War of Ideas: How the Muslim Identity is Being Redefined (Farah Pandith)
About the Editors
About the Contributors
Includes bibliographical references
Keywords: Religion and politics; Identity politics; Nationalism -- Religious aspects